PENGARUH LOCUS OF CONTROL DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA DI ERA SOCIETY 5.0 PADA MAHASISWA STKIP PERSADA KHATULISTIWA SINTANG - Sore, Avelius Dominggus; Fitriani, Maria Selvi; Suriyanti, Yulia (STKIP Persada Khatulistiwa Sintang, 2024)
This study aims to determine locus of control and entrepreneurship education in STKIP Persada Khatulistiwa Sintang students, interest in entrepreneurship in the era of society 5.0 in STKIP Persada Khatulistiwa Sintang students, and the influence of locus of control and entrepreneurship education on interest in entrepreneurship among STKIP Persada Khatulistiwa Sintang students. The method used in this research is quantitative and the form of this research is multiple regression. The population in this study were 790 students who had taken entrepreneurship education courses. The sample used was 100 students. The results showed that locus of control in STKIP Persada Khatulistiwa Sintang students showed a probability value of 0.000001 which was smaller than the significance level of 0.05 (5%), which means it was in the low category, while entrepreneurship education in STKIP Persada Khatulistiwa Sintang students showed a probability value of 0.094144 is greater than the significance level of 0.05 (5%) which means it is in the high category. There is a significant influence of locus of control and entrepreneurship education on the interest in entrepreneurship of STKIP Persada Khatulistiwa Sintang students with r2 = 0.495454 or 49.5% and the significance level of the locus of control variable is 0.0000 <0.05 and the significance level of entrepreneurship education is 0.0003 <0.05 with the condition that tcount > ttable, namely locus of control of 4.955023 > 1.98 and entrepreneurship education of 3.797132 > 1.98. Based on the results of the study, it can be concluded that locus of control and entrepreneurship education have an effect on interest in entrepreneurship in the era of society 5.0 in STKIP Persada Khatulitiwa Sintang students.